Peran Humas DPW LDII Sumatera Barat dalam Membangun Pilar Solidaritas dan Keharmonisan Sosial di Ranah Minang - Wulandari, Ilma; Prayudi, Muhammad Fariz; Latifah, Nahdia (Program Studi Ilmu Komunikasi Universitas Negeri Padang, 2024)
This research aims to analyze the role of Public Relations of the Indonesian Islamic Da'wah Institute (LDII) in communicating the vision, mission, and activities of the organization to the public and building a positive image of the organization. The research method used is qualitative with a case study approach. Data were collected through in-depth interviews with LDII's public relations officers, direct observation of public communication activities conducted by LDII, and analysis of documents and media publications issued by the organization. The results showed that LDII's PR plays a strategic role in disseminating information related to LDII's programs and activities, strengthening relationships with the media, and establishing effective communication with members and the wider community. LDII PR has also proven effective in building a positive image of the organization through a transparent, consistent, and responsive approach to issues in the community. This research provides insight into the important role of communication in religious organizations and the contribution of PR in supporting the achievement of LDII's goals.